THE INFLUENCE OF SERVICE QUALITY ON CUSTOMER LOYALTY (CASE STUDY AT CAFE UNCLE SAM LUBUK PAKAM) - Septiana Handayani Sagala; Sukaria Sinulingga; Sugiharto (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This research aims to test and analyze the influence of service quality on customer loyalty at Uncle Sam's Cafe. The entire population of Uncle Sam's cafe consumers. Determining the number of samples to use the formula is 5 times the number of indicator variables, totaling 24 indicators used, totaling 120 samples. The analysis technique used is multiple linear regression analysis. The research results prove that the influence of service quality using five indicators as research gaps is a factor causing customer loyalty, which has an impact on increasing the number of visitors to Uncle Sam's cafe. This is known from the respondents' answers where the respondents' perceptions regarding Tangibles, Reliability, Responsiveness partially have a positive and significant effect on Customer Loyalty at Uncle Sam's Cafe. Meanwhile, Assurance and Emphaty show that they partially have no significant effect on customer loyalty at Uncle Sam's Cafe. Simultaneous testing shows that Service Quality simultaneously influences Customer Loyalty at Uncle Sam's Cafe.